Pelatihan Bahasa Inggris Dasar Speaking Untuk Meningkatkan Motivasi dan Komunikasi Warga Kepada Pengunjung Taman Wisata Purbakala Sumpang Bita Kabupaten Pangkep - yati, sujariati; Sujariati, Sujariati; Jumiati, Andi Asri; Andi Baso, Farisa; Natsir, Ratu Yulianti; Firman, Firman (FKIP UKI TORAJA, 2022)
This training has done in Balocci district of Pangkep regency Sulawesi-selatan. This training aims to encourage the society in learning and speaking English, and improve their communication between staff of political district, society, citizen in the village of Balocci Pangkep regency, in ordering and confronting tourists and visitor include foreigner or peopple around the place who visiting the ancient park Sumpang Bita Pangkep. This training has done around two days by some lecturers from FKIP Muhammadiyah University of Makassar. And the result achievement was motivation improvement of participant in learning English and Vocabulary improvement in using for communication. The result or positive responses seemed by the participant responses in doing the learning activity, it also seemed by qustioning and answer came from the participant, and also seemed by the participant action and enthusiastic in following the training program.